2014
DOI: 10.1002/emmm.201303065
|View full text |Cite
|
Sign up to set email alerts
|

HIF factors cooperate with PMLRARα to promote acute promyelocytic leukemia progression and relapse

Abstract: Acute promyelocytic leukemia (APL) is epitomized by the chromosomal translocation t(15;17) and the resulting oncogenic fusion protein PML-RARα. Although acting primarily as a transcriptional repressor, PML-RARα can also exert functions of transcriptional co-activation. Here, we find that PML-RARα stimulates transcription driven by HIF factors, which are critical regulators of adaptive responses to hypoxia and stem cell maintenance. Consistently, HIF-related gene signatures are upregulated in leukemic promyeloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 36 publications
10
55
0
Order By: Relevance
“…Although our data indicate that in CLL, HIF-1a causes homing and retention in protective microenvironments, it is interesting to note that in other hematologic malignancies, including multiple myeloma and acute and chronic myeloid leukemia, hypoxia or HIF-1a activity instead induces cell egress and disease dissemination. 3,22,40,41 This difference may be caused by the selectivity of HIF-1a-mediated responses in different cell types, [42][43][44] such that adhesion factors may be regulated by HIF-1a specifically in CLL. Further studies should address in greater detail the specificity of HIF-1a activity in different tumor types, especially if HIF inhibitors will be considered for therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our data indicate that in CLL, HIF-1a causes homing and retention in protective microenvironments, it is interesting to note that in other hematologic malignancies, including multiple myeloma and acute and chronic myeloid leukemia, hypoxia or HIF-1a activity instead induces cell egress and disease dissemination. 3,22,40,41 This difference may be caused by the selectivity of HIF-1a-mediated responses in different cell types, [42][43][44] such that adhesion factors may be regulated by HIF-1a specifically in CLL. Further studies should address in greater detail the specificity of HIF-1a activity in different tumor types, especially if HIF inhibitors will be considered for therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Constitutive HIF-1a expression was suggested to induce vascular endothelial growth factor (VEGF) upregulation and neoangiogenesis. [19][20][21] However, because HIF-1a regulates a variety of other functions in solid tumors and hematologic malignancies, 1,22,23 we asked whether HIF-1a also controlled other aspects of CLL pathogenesis. Microarray analysis was performed upon stable HIF-1a silencing in the human CLL cell line MEC-1 ( Figure 1A-B), where HIF-1a is constitutively expressed in normoxia and further stabilized by the hypoxia-mimetic agent CoCl 2 ( Figure 1B).…”
Section: Hif-1a Regulates Chemotaxis and Adhesion To Stroma In Cllmentioning
confidence: 99%
“…Moreover, we found that HIF-1a expression is increased upon ATRA treatment, and mediates ATRA-induced increase in clonogenic activity in APL cells (12,14). Therefore, HIF-1a silencing synergizes with ATRA treatment in vivo to eradicate leukemia-initiating cells (LIC) and prevent leukemia relapse (12).…”
Section: Introductionmentioning
confidence: 93%
“…APL leukemic mice were obtained as previously described (10,12). Briefly, mice bearing PML-RARa-driven APL were obtained by transduction of Lin-bone marrow cells from 129/ Sv mice with a retroviral vector (pBABE backbone with DNGFR as a reporter) expressing PML-RARa (12).…”
Section: Migration Assaysmentioning
confidence: 99%
See 1 more Smart Citation